Urban Landscape Design Adaption to Flood Risk: A Case Study in Can Tho City, Vietnam. (September 2018) - Van Long, Nguyen; Cheng, Yuning
Located in the centre of the Mekong Delta (MD), Can Tho City (CTC), with a development history of more than three centuries, has affirmed its strategic position as an interregional centre. The city on Hau river is blessed by nature with the identity of a delta landscape associated with riverine dynamics. First, this article presents the development history of CTC, and the correlation between its urbanization history and the existing characteristics of the urban landscape. Then, this study further analyses challenges in urban development, assessing existing water infrastructure and opportunities of current urban and rural landscapes. Finally, urban landscape design strategies have been discussed to suggest improved resilience of the city with flood management in the context of climate change.